The Effect of Roe and Age of The Company on Value of The Companies - Intan Rahayu; Laras Pratiwi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
The company's obligation not only allows the company to maintain corporate profits, but the company must also be able to maintain the value of the company. Company value that can be offered from the price of the shares. There are many factors that can determine the value of a company, both financial and non-financial factors. Financial factors consist of company performance, while non-financial factors approved are old companies. This research studies the factors that can affect the value of the company, both financial and non-financial factors. The statistical analysis method used is a panel data regression. Panel data regression analysis is a combination of cross data (cross section) with time series data. The advantages of panel data regression analysis provide better, more varied data, reducing variables between variables, more degrees of freedom, and greater efficiency. This research was conducted at companies published on the Indonesia Stock Exchange with 2013-2017 research. The sampling technique uses stratified random sampling, which is to take proportional random samples.